Use of an operant paradigm for the study of antidepressant-induced sexual dysfunction. Issue 7 (October 2015) - Uphouse, Lynda; Pinkston, Jonathan; Baade, Duane; Solano, Christian; Onaiwu, Bless
Abstract : These studies were designed to develop a paradigm for the detection of antidepressant-induced sexual dysfunction in female rats. Ovariectomized, Fischer rats were conditioned to nose poke to open a guillotine door to gain access to a sexually active male. To develop the procedure, we examined the acquisition and stability of the response with a 15-s fixed interval, compared rats treated with 10 μg estradiol benzoate and 500 μg progesterone with those that received only estradiol benzoate, and carried out a preliminary analysis of the effects of 5, 10, and 15 mg/kg fluoxetine. We then more fully evaluated the effects of 5 mg/kg fluoxetine. Fluoxetine reduced sexual motivation, as assessed by the number of nose pokes, the number of nose poke episodes, and the latency to approach the male. In addition, changes in the females' sexual motivation were examined before and after ejaculation during the final conditioning trials. The number of nose pokes was reduced and the latency to initiate a new nose poke episode was increased following ejaculation. The robustness of the antidepressant-induced decline in sexual motivation is in marked contrast to the findings with several other animal models for sexual dysfunction and illustrates the usefulness of the operant procedure.